Conserved polynucleotide sequences among the genomes of papillomaviruses. - Law, M F (1979)
The DNAs of different members of the Papillomavirus genus of papovaviruses were analyzed for nucleotide sequence homology. Under standard hybridization conditions (Tm - 28 degrees C), no homology was detectable among the genomes of human papillomavirus type 1 (HPV-1), bovine papillomavirus type 2 (BPV-2), or cottontail rabbit (Shope) papillomavirus (CRPV). However, under less stringent conditions (i.e., Tm - 43 degrees C), stable hybrids were formed between radiolabeled DNAs of CRPV, BPV-1, or BPV-2 and the HindIII-HpaI A, B, and C fragments of HPV-1. Under these same conditions, radiolabeled CRPV and HPV-1 DNAs formed stable hybrids with HincII B and C fragments of BPV-2 DNA. These results indicate that there are regions of homology with as much as 70% base match among all these papillomavirus genomes. Furthermore, unlabeled HPV-1 DNA competitively inhibited the specific hybridization of radiolabeled CRPV DNA to bpv-2 DNA fragments, indicating that the homologous DNA segments are common among these remotely related papillomavirus genomes. These conserved sequences are specific for the Papillomavirus genus of papovaviruses as evidenced by the lack of hybridization between HPV-1 DNA and either simian virus 40 or human papovavirus BK DNA under identical conditions. These results indicate a close evolutionary relationship among the papillomaviruses and further establish the papillomaviruses and polyoma viruses as distinct genera.